1994
DOI: 10.1128/aem.60.10.3870-3873.1994
|View full text |Cite
|
Sign up to set email alerts
|

Glucose uptake by Listeria monocytogenes Scott A and inhibition by pediocin JD

Abstract: Glucose uptake by Listeria monocytogenes Scott A was inhibited by the bacteriocin pediocin JD and by the protonophore carbonyl cyanide m-chlorophenyhydrazone. Experiments with monensin, nigericin, chlorhexidine diacetate, dinitrophenol, and gramicidin, however, showed that glucose uptake could occur in the absence of a proton motive force. L. monocytogenes cell extracts phosphorylated glucose when phosphoenolpyruvate (PEP) was present in the assay mixture, and whole cells incubated with 2-deoxyglucose accumula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 19 publications
3
11
0
1
Order By: Relevance
“…In addition to dissipation of PMF, bacteriocins are reported to deplete intracellular adenosine triphosphate (ATP), either through leakage or hydrolysis, and to cause efflux of intracellular inorganic phosphate (P i ) (Abee et al 1994a;Abee et al 1994b;Winkowski et al 1994;Chen and Montville 1995). Some bacteriocins also inhibit uptake and induce efflux of nutrients such as amino acids and sugars (van Belkum et al 1991;Venema et al 1993;Christensen and Hutkins 1994).…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…In addition to dissipation of PMF, bacteriocins are reported to deplete intracellular adenosine triphosphate (ATP), either through leakage or hydrolysis, and to cause efflux of intracellular inorganic phosphate (P i ) (Abee et al 1994a;Abee et al 1994b;Winkowski et al 1994;Chen and Montville 1995). Some bacteriocins also inhibit uptake and induce efflux of nutrients such as amino acids and sugars (van Belkum et al 1991;Venema et al 1993;Christensen and Hutkins 1994).…”
Section: Introductionsupporting
confidence: 56%
“…Glucose uptake assays were started by addition of [ 14 C]glucose (3·7 mCi mmol −1 ; Sigma Radiochemicals, St. Louis, MO, USA) to cell suspensions to give a final concentration of either 15 mmol l −1 (PMF-mediated transport) or 0·5 mmol l −1 (PEP-dependent PTS). Mixtures were incubated at room temperature and, at regular intervals, 1 ml samples of cell suspension were removed and centrifuged through silicon oil (12 000 g for 2 min) (Christensen and Hutkins 1994). Radioactivity was determined by liquid scintillation counting as described previously (Parker and Hutkins 1997).…”
Section: Glucose Uptake Assaysmentioning
confidence: 99%
“…It was reported that glucose PEP:PTS activity in four L. monocytogenes strains was inhibited by the bacteriocins nisin, pediocin JD and leuconocin S (Waite et al 1998). Inhibition of the PEP:PTS in L. monocytogenes Scott A by pediocin JD was also reported previously (Christensen and Hutkins 1994). In the presence of pediocin JD and exogenous PEP, phosphorylation of glucose by permeabilized L. monocytogenes Scott A cells decreased 86% (Christensen and Hutkins 1994).…”
Section: Introductionsupporting
confidence: 79%
“…Inhibition of the PEP:PTS in L. monocytogenes Scott A by pediocin JD was also reported previously (Christensen and Hutkins 1994). In the presence of pediocin JD and exogenous PEP, phosphorylation of glucose by permeabilized L. monocytogenes Scott A cells decreased 86% (Christensen and Hutkins 1994).…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation